Effect of microfin surfaces on boiling heat transfer using HFE-7100 as working fluid - Kiyomura, Igor Seicho [UNESP] (2020)
One promising way to enhance the heat transfer coefficient (HTC) and the critical heat flux (CHF) is modifying the heating surface morphology by using machining techniques, coating, and chemical processes. Microstructured surfaces, i.e., surfaces with the presence of micropillars on the surface, provide small perturbations in the liquid, affecting the vapor bubbles dynamic. These structures increase the heating surface area and change the fluid flow. Microfins can have different shapes and sizes and can be arranged in different patterns to improve heat transfer. This study aims to evaluate experimentally the thermal performance of different microfin surfaces by using HFE-7100 as working fluid. Square micro-pillar arrays were etched on a plain copper surface through the micro-milling process. Square microfins of different length scales (i.e., height and side length) were uniformly spaced on the plain copper surface. The inter-fin space had the same value, 250 μm, for all surfaces in order to control the effective roughness, Reff, defined as the ratio of the area in contact with the liquid to the projected area. Microfin surfaces intensify the HTC as compared to plain surfaces and the number of fins is the main factor for the HTC enhancement; if the number of microfins is constant, the larger the effective roughness, the higher the heat transfer performance. Additionally, the capillary-wicking ability increases and it also improves the HTC and the dryout heat flux due to the prevention of hotspots in the microfin surface. Thus, the surface thermal behavior is a function of the surface morphology and its surface capillary wicking.